Oxidative stress induced by silica-coated iron oxide nanoparticles in SHSY5Y neuronal cells - Kiliç, G. (2016)
Nanotechnology industry is progressing with prospects of substantial benefits to economics and science. Superparamagnetic iron oxide nanoparticles (ION) have been showing excellent magnetic properties, biocompatibility and biodegradability, broadening their potential applications and importance in the biomedical field. Nevertheless, there are increasing concerns as to the potential adverse effects on human health and environment and, currently, data on the effects of ION on the human nervous system are controversial.